Hollow Nickel–Cobalt Layered Double Hydroxide Supported Palladium Catalysts with Superior Hydrogen Evolution Activity for Hydrolysis of Ammonia Borane. Issue 15 (25th May 2018) - Zhou, Ying‐Hua; Wang, Suqin; Zhang, Zhiyan; Williams, Nicholas; Cheng, Yong; Gu, Jing
Abstract: Although ammonia borane (NH3 BH3, AB) has been identified as an excellent hydrogen‐storage medium, the development of a highly active catalyst that can function under mild conditions for controllable hydrogen release is still a great challenge. The synergistic effect induced by interactions between metal nanoparticles and a support has been widely applied in thermocatalytic conversion processes. In this work, Pd nanoparticles (NPs) highly dispersed on hollow NiCo layered double hydroxide (LDH) were designed for efficient hydrogen generation from AB at room temperature. During the hydrolytic dehydrogenation of AB, Pd/α‐LDH and Pd/β‐LDH exhibited catalytic activities with total turnover frequency (TOF) values of 49.5 and 28.1 min −1 with activation energy ( E a ) values of 20.56 and 37.56 kJ mol −1, respectively, at 298 K; thus, these catalysts outperform most Pd‐based catalysts. The improved catalytic effect was attributed to the controllable size and fine distribution of the Pd NPs and the collaborative effect provided by the hydroxide of α‐LDH and the intercalated anions (HO − ). This catalysts design principle can be easily transferred to other catalyst research fields for energy‐conversion and ‐storage purposes. Abstract : Layer of darkness : Pd nanoparticles (NPs) are highly dispersed onto the hollow NiCo layered double hydroxide (LDH) derived from ZIF‐67 through an in situ reduction method. The nanocomposite exhibits superior catalytic performance for hydrogen generation from ammonia borane in aqueous solution at room temperature.